PENANGANAN MANDIRI EMESIS GRAVIDARUM PADA IBUHAMILDI BPM HJ. NINIK ARTINGINGSIH,SST., M.KES KELURAHAN BLOOTOKECAMATANPRAJURIT KULON KOTA MOJOKERTO - Wahyuningrum, Tria; Virda Yuniarti, Enny (JURNAL KEPERAWATAN SEHAT, 2016)
Nausea and vomiting one of the most common early symptom and cause most of the stress associated with pregnancy. Nausea and vomiting are often overlooked because it is regarded as a normal consequence of the beginning of pregnancy without knowing the great impact it has had on pregnant women, especially in the fetus. Pregnant women do not have enough knowledge about morning sickness because of the lack of experience of the subject, so it can not determine the action that should be done. This research aims to determine independently handling morning sickness in pregnant women in BPM Hj. Ninik Artiningsih, SST., M. Kes Kelurahan Blooto Kecamatan Prajurit Kulon Kota Mojokerto. This research use descriptive method with variable self handling morning sickness. The research population was all pregnant women have experienced morning sickness on May 2016 total of 33 people in BPM Hj. Ninik Artiningsih, SST., M. Kes Kelurahan Blooto Kecamatan Prajurit Kulon Kota Mojokerto. The sampling technique used is consecutive sampling. The results showed that selfhandling morning sickness in pregnant women in BPM Hj. Ninik Artiningsih, SST., M. Kes Kelurahan Blooto Kecamatan Prajurit Kulon kota Mojokerto most are quite good, as many as 15 people (60%). Analysis of the data used is the frequency distribution table. Education level and occupation of respondents influence the handling of independently conducted by the respondent, where the higher education respondents would make respondents more easier to find information, and respondents who become housewives have more time so that it can carry out the handling independently against morning sickness.Keywords:Morning sickness,pregnancy, selfhandling.